Early experience with the “modified jailed balloon technique” for side branch protection in bifurcation lesions - Somyata Somendra; Himanshu Gupta; Yash Paul Sharma (Indian Heart Journal)
Objective: M-JBT is a novel approach to the ''keep-it-open strategy'' for bifurcation lesions where SB anatomy is unsuitable for stenting. We intend to provide insight into a contemporary way through our experience of the M-JBT. Methods: A semi-compliant balloon sized appropriately for the SB diameter is inflated simultaneously with the MB stent balloon during stent deployment, followed by POT of the MB stent and then recrossing the SB. Results: We performed the “M-JBT” in 25 cases of bifurcation lesions between September 2023–24, with absolute procedural success in preventing SB occlusion during MB stenting in all 25 lesions. SB occlusion after MB stent POT was seen in one case. Conclusion: This is the first report of clinical experience with the MJBT from the Indian subcontinent. MJBT proves to be a safe and effective approach to the protection of a clinically important SB during MB stenting across it.